Qolbil Qur’an: Internalization of Quranic Values in Strengthening Students’ Religious Character at MI Terpadu Al Falah - Ahmad Nurul Fahmi; M. Sofyan Alnashr; Miftakhul Munif (MAGISTRA: Media Pengembangan Ilmu Pendidikan Dasar dan Keislaman, 2025)
Moral degradation among elementary school students underscores the urgent need for character education models that transcend mere cognitive instruction toward systematic value habituation. This study analyzes the social construction of religious character through the “Qolbil Qur’an” program at MI Terpadu Al Falah, which uniquely adapts traditional Sufistic values (thoriqoh) into a primary school curriculum. Employing a qualitative case study design, data were analyzed using Peter L. Berger’s Social Construction theory (externalization, objectivation, internalization) integrated with Thomas Lickona’s character framework. The findings reveal a dialectical process: Externalization is evident in the founder’s vision of transforming spiritual traditions into a child-friendly pedagogical program. Objectivation occurs through the institutionalization of morning routines, the sanctity of the Qolbil Qur’an booklet, and teacher modeling. Crucially, the internalization process exhibits a distinct dynamic: while deep cognitive understanding (moral knowing) poses challenges due to rote memorization, strong value internalization occurs through the affective-habituation pathway (unconscious habituation). Consequently, students manifest profound moral character, as evidenced by respectful etiquette, disciplined worship, and emotional stability. The study concludes that structured Qur’anic habituation serves as an effective social mechanism for character building, offering a strategic model for contextualizing spiritual traditions within modern education.